Evaluasi Terhadap Implementasi Kurikulum Merdeka - Ibrahim Ibrahim; Maulana Zakaria; Rani Pratiwi; Marisa Adelia; Desti Flauren Zakira (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study discusses the evaluation of the implementation of the